Islamic banking: fiqh muasarah view on modern financial transaction / Jalaluddin Mahamod … [et al.] - Mahamod, Jalaluddin; Aziz, Muhammad Amirul Firdaus; Dzalihu'zzabir, Muhammad Fakhrul Hadi; Ruslan, Muhammad Fauzan (2023)
This paper explores the implications of Shariah maxims on modem financial transactions,. emphasizing key principles such as intentions and acts, doubt and certainty, rules of necessity, offering and obtaining, and limitations. The study delves into the foundational principle that "Acts are judged by the intention behind them," elucidating its relevance in various contexts, including financial dealings. It highlights the importance of disclosing banking policies and avoiding practices that contradict Islamic principles. The discussion on doubt and certainty underscores the rejection of doubt in favour of certainty in legal matters. The paper then delves into issues in modern financial transactions, particularly in the era of globalization and digital finance. Security and confidentiality of data emerge as critical challenges, necessitating the implementation of robust measures, including two-factor authentication and encryption, in compliance with Shariah principles. Infrastructure security is also addressed, emphasizing the need for protection against cyber threats while adhering to Shariah tenets related to data use and privacy. Furthermore, the study identifies Shariah law risks associated with the use of digital financial technology. It emphasizes the importance of valid signatures in digital contracts and proposes a comprehensive mechanism, guided by maqasid to mitigate sharia law risks effectively. The role of sharia experts in planning and implementing digital financial technology is highlighted to ensure compliance with Islamic principles. In summary, this paper provides a comprehensive analysis of the implications of Shariah maxims on modern financial transactions, addressing contemporary challenges and proposing measures to ensure compliance with Islamic principles in the evolving landscape of global finance.